Comparative Pathology and Immunohistochemistry of Veterinary Species - Suárez-Bonnet, Alejandro; Ramírez Rivero, Gustavo A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Comparative pathology, translational research, and clinical trials involving domestic animals have the ultimate goal of advancing our medical knowledge of both human and veterinary species. Companion, laboratory (from mouse to non-human primates), and wildlife animals play a pivotal role in our understanding of infectious diseases-particularly those with a zoonotic component. This reprint focuses on fundamental and applied research on the comparative pathology and immunohistochemistry of veterinary species. A total of 11 high-quality papers addressing different areas of pathology have been contributed by 62 authors from seven countries, comprising 9 research articles and 2 communications.